Some metabolic responses to reduced breathing frequency during constant load exercise - Kapus, J.; Ušaj, A.; KapusV. (2009)
The article compares swimming vs. dry land activities, explains the breathing in front crawl swimming and bicycling in usual and reduced breathing conditions, e. g. under hypoxic conditions. The purpose of the study is to compare metabolic responses (ventilatory, gas exchange and oxygen saturation) during the constant load bicycle exercise with two different breathing conditions (spontanuous breathing and RBF).